PMOSFET PBTI (positive-bias temperature instability) measurement using ultra-fast switching method - Huang, Baoqiang. (2009)
Similar to negative bias temperature instability (NBTI), positive bias temperature instability (PBTI) also causes the build-up of positive charge in the gate dielectric of the p-MOSFET, resulting in threshold voltage (VT) increase and drain current decrease, which eventually lead to circuit failure. Although, NBTI had been research intensively, but the actual mechanism to it has not been verify. Thus, PBTI in p-MOSFET is experimented in this project to understand the difference in the temporal behaviour of PBTI and NBTI by using Ultra Fasting Switching (UFS) technique while maintaining the focus in PBTI. In order to understand more on PBTI, topics that are relevant to subsequent results were first review. The topics included PBTI and NBTI phenomena, interface traps and oxide charges, reaction and diffusion(R-D) model, hydrogen effect and nitrogen effect. Ultra Fast Switching (UFS) techniques were then apply to test the devices. Setting up of experiment will also be included to set as a reference for future work. Data used in the report would include thin (1.9nm) and thick (3nm) SiON dielectric of p-MOSFET in PBTI and having the thick (3nm) dielectric going through NBTI. NBTI has shown to cause negative threshold voltage shift throughout the stress voltage. However, PBTI has observed to have an initial positive threshold voltage shift in low stress voltage and slowly evolving into negative threshold voltage shift at higher stress voltage. A possible explanation to the phenomenon will be state in the report. A comparison with NBTI and PBTI will also be included in the discussion in the field of electric-field dependence and nitrogen effect.